NILAI ANKLE BRACHIAL INDEX (ABI) DENGAN NEUROPATI PERIFER DIABETIK PADA PASIEN DIABETES MELITUS TIPE 2 - I Dewa Putu Gede Putra Yasa (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
The study aims to determine relationship between value ankle brachial index (ABI)and diabetic peripheral neuropathy on type 2 DM patients at public health center of I Klungkung. This study used an analytic correlational design with cross sectional approach. The sample this study were 82 person and was selected by using purposive sampling techniques. The results of the study found that the average age of respondents was 67.8 years, the average duration of DM respondents was 7.26 years, 61.0% of respondents were female, 42.7% of respondents had neuropathy and 32.9% had ABI for vascular disorders. The conclusion of this study is that there is a significant relationship between value ankle brachial index (ABI) and diabetic peripheral neuropathy (p = 0,000) and value of Odd Ratio = 1.45 which means that type 2 DM patients who experience vascular disorders have 1.45 times the chance of neuropathy peripheral diabetics.